Comparative Studies on Decomposition of Leaf Litter in Teak Plantation - Rajagopal, K.; Buvaneswaran, C.; George, M.; Manivachagam, P. (Indian Forester, 2005)
Comparative studies on litter decomposition employing two methods - bag and non-bag, were carried out under teak plantation of age 30 years. Though a steady decline in decomposition of the litter occurred in both the cases, the rate of decomposition was faster in the non-bag method than that of the bag. The un-decomposed litter after a period of one year was 19.43% in non-bag method against 49.8% in the bag method. The decomposition coefficient (k) was higher in non-bag (1.638) when compared to bag method (0.697). With regard to nutrients in the decomposing litter, the concentration of different nutrients differed as the decomposition progressed. Among the nutrients (N, P, K, Ca and Mg), the release of potassium was faster when compared to others. Between the two methods the decomposition co-efficient (k) was greater for all nutrients in non-bag method.